Peningkatan Kualitas Stek Pucuk Krisan (Chrysanthemum morifolium) melalui Pemberian Indole-3-Butyric Acid sebagai Zat Pengatur Tumbuh. - Vidia Pangestika; Karno Karno; Budi Adi Kristanto (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
Chrysanthemum is one of popular floriculture commodities in Indonesia. Chrysanthemum is mainly propagated by terminal cutting. This study aimed to investigate the rooting and vegetative growth response of three different cultivars of chrysanthemum cutting treated by different level of IBA. The experiment was assigned in a completely randomized design on propagation phase and randomized block design on planting phase. The first factor was cultivar which consist of 3 varieties : V1 = Puspita Nusantara, V2 = Fiji, V3 = Dewi Ratih. The second factor was IBA level which consists of 4 levels : D0=0 ppm, D1= 200 ppm, D2= 400 ppm, D3= 600 ppm. The experiment was replicated 4 times. Parameters measured were number of roots, root length, root weight, shoot fresh weight and shoot dry weight. The data were analyzed statistically by analysis of variance and followed by Duncan test. The result showed that number of roots, root length, and root weight were significantly affected by variety treatment and IBA dose treatment. plant height and number of leaves were significantly affected by variety treatment. There was no influence of IBA dose treatment on plant height and number of leaves. Keywords : indole-3-butyric acid, cuttings, chrysanthemum